2023
DOI: 10.15517/am.v34i2.52131
|View full text |Cite
|
Sign up to set email alerts
|

The effect of processing and storage on Klanceng honey (Tetragonula laeviceps)

Abstract: Introduction. Klanceng honey (Tetragonula laeviceps) is in great demand because of its benefits. There is no information on the expiration date of the Klanceng honey. Objective. To predict the shelf life of Klanceng honey by evaluating the effect of heating (40 ºC / 48 h and 70 ºC / 7 h) and storage for two years. Materials and methods. The analysis was carried out three times (2020, 2021, and 2022) at the National Innovation Research Agency Laboratory, Jakarta, Indonesia. Samples of Klanceng honey (Tetragonul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Most previous studies showed a statistically significant difference in 5-HMF content during storage at different temperatures (Table 1). For example, Kędzierska-Matysek et al ( 2016) reported an increase from 3.07 to 19.74 mg/kg during storage period of 18 months at storage temperature of 20-26 • C. Budianto et al (2023) reported that the 5-HMF content of honey increased from 3.5 to 34.84 mg/kg at 25-27 • C during the storage period of 24 months. Czipa et al ( 2019) reported a rise from 1.89 to 13.60 mg/kg during storage of 24 months at 20 • C. The increase in 5-HMF content in honey samples is usually due to the breakdown of sugars, resulting in more 5-HMF being formed.…”
Section: -Hmf Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies showed a statistically significant difference in 5-HMF content during storage at different temperatures (Table 1). For example, Kędzierska-Matysek et al ( 2016) reported an increase from 3.07 to 19.74 mg/kg during storage period of 18 months at storage temperature of 20-26 • C. Budianto et al (2023) reported that the 5-HMF content of honey increased from 3.5 to 34.84 mg/kg at 25-27 • C during the storage period of 24 months. Czipa et al ( 2019) reported a rise from 1.89 to 13.60 mg/kg during storage of 24 months at 20 • C. The increase in 5-HMF content in honey samples is usually due to the breakdown of sugars, resulting in more 5-HMF being formed.…”
Section: -Hmf Contentmentioning
confidence: 99%
“…Budianto et al. (2023) reported that the 5‐HMF content of honey increased from 3.5 to 34.84 mg/kg at 25–27°C during the storage period of 24 months. Czipa et al.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%